The Value of Lung Ultrasound Score in Neonatology - Zong, Haifeng; Huang, Zhifeng; Zhao, Jie; Lin, Bingchun; Fu, Yongping; Lin, Yanqing; Huang, Peng; Sun, Hongyan; Yang, Chuanzhong (Frontiers in Pediatrics, 2022)
Point-of-care lung ultrasound (LUS) is increasingly applied in the neonatal intensive care unit (NICU). Diagnostic applications for LUS in the NICU contain the diagnosis of many common neonatal pulmonary diseases (such as Respiratory distress syndrome, Transient tachypnea of the newborn, Meconium aspiration syndrome, Pneumonia, Pneumothorax, Pleural effusion, and Congenital diaphragmatic hernia) which have been validated. In addition to being employed as a diagnostic tool in the classical sense of the term, recent studies have shown that the number and type of artifacts are associated with lung aeration. Based on this theory, over the last few years, LUS has also been used as a semi-quantitative method or as a “functional” tool. Scores have been proposed to monitor the progress of neonatal lung diseases and to decide whether or not to perform a specific treatment. The semi-quantitative LUS scores (LUSs) have been developed to predict the demand for surfactant therapy, the need of respiratory support and the progress of bronchopulmonary dysplasia. Given their ease of use, accuracy and lack of invasiveness, the use of LUSs is increasing in clinical practice. Therefore, this manuscript will review the application of LUSs in neonatal lung diseases.